Quantum key distribution protocols in transmission control protocol - Kamarul Aizan, Nur Hanani (2012)
A quantum key distribution (QKD) system produced shared secret key and transmitted the key between the sender and receiver in a highly secured transmission. QKD uses the fundamental of quantum properties of a single photon to provide a secured communication channel with absolute security guaranteed by the laws of physics. This research has developed a simulator software for BB84 and B92 protocols which implemented both protocols in 802.11i WLAN environment. The parameters used for this research are with attack and without attack, where measured by three measurements for both protocols which are final key length, expected key length by eavesdropper and error rate estimation. The 802.11i WLAN is consider as insecure because the tendency to be intercepted by intruders is high. Furthermore, the interference from other consumer devices such as cordless phone and microwave can contribute to degradation of WLAN performance. This type of noise can generate different numbers of final key length and different levels of error rate estimation. Thus, the level of the error rate estimation determined the secrecy of the secret key. The discussion of security issue between BB84 and B92 protocols also discussed in terms of secrecy and strength of the secret key between both protocols in 802.11i WLAN.